A comparative study of the TF-Test®, Kato-Katz, Hoffman-Pons-Janer, Willis and Baermann-Moraes coprologic methods for the detection of human parasitosis - Gabriela Lanna Xavier de Carvalho; Luciano Evangelista Moreira; João Luiz Pena; Carolina Coimbra Marinho; Maria Terezinha Bahia; George Luiz Lins Machado-Coelho (Memorias do Instituto Oswaldo Cruz, 2012)
This study compares the diagnostic accuracy of the TF-Test® (TFT) for human parasitosis with results obtained using the traditional Kato-Katz (KK), Hoffman-Pons-Janer (HPJ), Willis and Baermann-Moraes (BM) techniques. Overall, four stool samples were taken from each individual; three alternate-day TFT stool samples and another sample that was collected in a universal container. Stool samples were taken from 331 inhabitants of the community of Quilombola Santa Cruz. The gold standard (GS) for protozoa detection was defined as the combined results for TFT, HPJ and Willis coproscopic techniques; for helminth detection, GS was defined as the combined results for all five coproscopic techniques (TFT, KK, HPJ, Willis and BM). The positivity rate of each method was compared using the McNemar test. While the TFT exhibited similar positivity rates to the GS for Entamoeba histolytica/dispar (82.4%) and Giardia duodenalis (90%), HPJ and Willis techniques exhibited significantly lower positivity rates for these protozoa. All tests exhibited significantly lower positivity rates compared with GS for the diagnosis of helminths. The KK technique had the highest positivity rate for diagnosing Schistosoma mansoni (74.6%), while the TFT had the highest positivity rates for Ascaris lumbricoides (58.1%) and hookworm (75%); HPJ technique had the highest positivity rate for Strongyloides stercoralis (50%). Although a combination of tests is the most accurate method for the diagnosis of enteral parasites, the TFT reliably estimates the prevalence of protozoa and selected helminths, such as A. lumbricoides and hookworm. Further studies are needed to evaluate the detection accuracy of the TFT in samples with varying numbers of parasites.